An Analysis of Empowering Underprivileged Families through Program Keluarga Harapan from a Weberian Perspective - Adam Hafidz Al Fajar; Elfira Zidna Almaghfiro (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2024)
This article examines the empowerment of underprivileged families through Program Keluarga Harapan (PKH) from a Weberian perspective. In the 21st century, the PKH has emerged as one of Indonesia’s governmental efforts to empower underprivileged families. This study focuses on the implementation of PKH in Bongas Kulon Village, emphasizing the importance of fostering family welfare empowerment through various initiatives, including the disbursement of social assistance funds and the Family Capacity Building Meetings (P2K2), through the lens of Max Weber’s classical sociological theory. The study aims to understand the motivations and social drivers behind the behavior of participants engaged in this empowerment program. A qualitative research approach was employed, using data collection methods such as interviews, observations, and document analysis. Findings reveal that the implementation of the PKH program involves several stages: preparation, execution, evaluation, and termination. The empowerment program has demonstrated positive impacts on aspects such as early childhood health, education, and elderly welfare by improving access to educational and health facilities. This research contributes to both practical and theoretical understandings of the effectiveness of family empowerment programs by integrating Max Weber’s classical sociological theory.